Experimental analysis of an innovative organic membrane for air to air enthalpy exchangers. (November 2019) - Baldinelli, Giorgio; Rotili, Antonella; Narducci, Riccardo; Di Vona, Maria Luisa; Marrocchi, Assunta
Abstract: In recent years, ventilation of indoor environment became relevant in the design of well-insulated buildings; with the aim of fulfilling energy saving requirements, new building mechanical ventilation systems have been developed to guarantee heat recovery. The most common heat recovery systems used in air conditioning systems permit only heat recovery, without moisture exchange. However, exchangers capable to recover heat and mass have been developed in the latest years, i.e. the enthalpy exchangers, which use porous materials or membranes. These materials allow the transfer of water vapor molecules between inlet and outlet air. In the present paper the performance of an original and innovative organic polymeric membrane was analysed and compared to a commercial one. The effectiveness of the two membranes was tested by a single plate enthalpy exchanger developed for this purpose, looking at the ability of each membrane to transfer heat and moisture between two airstreams, varying their temperature and relative humidity. Results shows that both membranes have similar performance in terms of moisture transfer between the two airstreams, confirming that the proposed membrane could play a role in the world of the enthalpy exchangers, considering its lower production cost. Highlights: An innovative membrane is developed for air enthalpy exchangers. An experimental air enthalpy exchanger has been especially built for this purpose. The latent and sensible effectiveness of an innovative and a commercial membrane one was analysed and compared. The innovative membrane shows itself suitable to be used in energy recovery systems.